Improving The Learning Outcomes Of Volleyball Top Passing By Using A Standard Ball In Class Xi Ips 1 SMA Negeri 7 Bengkulu Utara - Pratama, Bayu Aji; Mesterjon, Mesterjon; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study aims to improve the Learning Outcomes of Volleyball Upper Passing Using Standard Balls in Class XI IPS 1 SMA Negeri 7 Bengkulu Utara with the type of PTK research with the test method with a total sample of 22 students in class XI IPS. The results showed that the initial data of the volleyball upper passing skills test showed that students who reached the KKM were 14%, namely 3 students were complete, 19 students were not complete (86%). In cycle one the first meeting there was an increase in completeness of 59%, namely 13 students completed and 9 students did not complete (41%). Then in cycle one the second meeting there was an increase in completeness of 68%, namely 15 students were complete and 7 students were not complete (32%) after that in cycle two the first meeting there was an increase in completeness of 73%, namely 16 students were complete and 6 students were not complete (27%). In cycle two the second meeting there was an increase in completeness of 82%, namely 18 students and 4 students (18%). In this study, using a standard ball can improve the learning outcomes of volleyball top passing.